2021
DOI: 10.3201/eid2708.204318
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Disease Surveillance, Mississippi, USA

Abstract: H uman populations in the state of Mississippi and the rest of the southeastern United States have historically been at risk for hookworm and other parasitic diseases (1,2). With improved sanitation and economic development, soil-transmitted helminths (STH), including the species Ascaris lumbricoides and Trichuris trichiura, were presumed to have been eliminated. However, a recent report of continued hookworm and strongyloidiasis transmission in a community without access to proper sanitation in Alabama, USA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…For population-based surveillance, the UMMC source population was defined as residents of a 16-county area including the state capitol of Jackson, Mississippi, for whom UMMC is the nearest acute care hospital, based on prior convenience sample surveillance studies. 5 According to 2019 bridged US Census estimates, racial and ethnic composition of the 16-county area (population, 1,080,808) was 49% non-Hispanic Black, 46% non-Hispanic White, and 5% Hispanic or other race/ethnicity. 6 References to Black and White race herein refer to non-Hispanic Black and White, specifically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For population-based surveillance, the UMMC source population was defined as residents of a 16-county area including the state capitol of Jackson, Mississippi, for whom UMMC is the nearest acute care hospital, based on prior convenience sample surveillance studies. 5 According to 2019 bridged US Census estimates, racial and ethnic composition of the 16-county area (population, 1,080,808) was 49% non-Hispanic Black, 46% non-Hispanic White, and 5% Hispanic or other race/ethnicity. 6 References to Black and White race herein refer to non-Hispanic Black and White, specifically.…”
Section: Methodsmentioning
confidence: 99%
“…The University of Mississippi Medical Center provides clinical laboratory services for university hospitals in central Mississippi and associated university network clinics statewide (5). Beginning in May 2020, residual serum and plasma from patient blood specimens submitted to the UMMC central laboratory for diagnostic testing were collected for those <18 years of age.…”
Section: Sars-cov-2 Antibody Seroprevalencementioning
confidence: 99%
“…2 Two recent studies from Mississippi found little evidence of STH infection in stool and serology from 166 children living in the Mississippi delta and from patients treated at a Mississippi medical center. 10,11 Sixteen percent (331/ 2,056) of all pediatric visits for helminth infections during our study time period occurred in the Black Belt, which is proportionate to the 15% of Medicaid-eligible children in Alabama reported to live in those same counties during 2017, 8 suggesting that residence in a Black Belt county may be less important compared with other factors when determining STH risk. Evidence remains insufficient to determine the degree to which STH endemicity exists in Alabama.…”
mentioning
confidence: 89%
“…There is an endemic pattern to the incidence and prevalence of strongyloidiasis in the USA. It has been noticed that outbreaks have occurred in the Northeastern and Southeast regions of the USA,1–3 as a result of inadequate sanitation in underprivileged and marginalised communities 4. Immunosuppressive medications, pregnancy, cancer, HIV infection, malnutrition and alcoholism are risk factors for developing strongyloidiasis 5…”
Section: Introductionmentioning
confidence: 99%